2013
DOI: 10.1111/psyp.12161
|View full text |Cite
|
Sign up to set email alerts
|

Virtually simulated social pressure influences early visual processing more in low compared to high autonomous participants

Abstract: In a previous study, we showed that virtually simulated social group pressure could influence early stages of perception after only 100  ms. In the present EEG study, we investigated the influence of social pressure on visual perception in participants with high (HA) and low (LA) levels of autonomy. Ten HA and ten LA individuals were asked to accomplish a visual discrimination task in an adapted paradigm of Solomon Asch. Results indicate that LA participants adapted to the incorrect group opinion more often th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
(60 reference statements)
2
4
0
Order By: Relevance
“…After all, seeking social proof and identifying congruency with versus deviance from the group is no end in itself, but should inform subsequent processing and behavior. Our finding is thus consistent with previous work suggesting that majority cues (such as the majority's actual response or its divergence from one's own views) preceding the analysis of to‐be‐judged items can affect the basic representation of these stimuli via modulations of early and fundamental stages of processing (Berns et al, ; Germar et al, ; Trautmann‐Lengsfeld & Herrmann, ; Zaki et al, ). In addition to the reinforcing effect of agreeing, such direct modulations represent an alternative neurocognitive principle of social influence (Schnuerch & Gibbons, ).…”
Section: Discussionsupporting
confidence: 92%
“…After all, seeking social proof and identifying congruency with versus deviance from the group is no end in itself, but should inform subsequent processing and behavior. Our finding is thus consistent with previous work suggesting that majority cues (such as the majority's actual response or its divergence from one's own views) preceding the analysis of to‐be‐judged items can affect the basic representation of these stimuli via modulations of early and fundamental stages of processing (Berns et al, ; Germar et al, ; Trautmann‐Lengsfeld & Herrmann, ; Zaki et al, ). In addition to the reinforcing effect of agreeing, such direct modulations represent an alternative neurocognitive principle of social influence (Schnuerch & Gibbons, ).…”
Section: Discussionsupporting
confidence: 92%
“…Changes have been attributed to hormonal factors, especially with regard to puberty influencing both brain structure and function (67, 68). Our own results, and results from EEG and drift diffusion modeling in adults, converge on a model in which social influence biases already early sensory processing (6, 7, 6971). Sensory signals that contribute to the reported percept for the stereomotion visual task in this study have been linked to primate visual area V5/MT, which is located on the posterior bank of the superior temporal sulcus (STS) in rhesus macaques (34, 35).…”
Section: Discussionsupporting
confidence: 78%
“…Additionally, to the best of our knowledge, previous studies or reviews neither reported nor discussed gender differences in the neurocognitive mechanism of social influence (e.g. Schnuerch and Gibbons, 2014;Trautmann-Lengsfeld and Herrmann, 2014). Thus, although research using the Asch paradigm consistently revealed higher levels of conformity for female than for male participants (Bond and Smith, 1996), there is insufficient evidence to suggest that this difference is due to qualitative gender differences in the mediating neurocognitive mechanisms.…”
Section: Limitationsmentioning
confidence: 77%